Analisis Kebutuhan Pengembangan Komik Digital IPA Berbasis Kearifan Lokal Pada Materi Ekosistem Untuk Siswa Kelas V SD di Gugus 2 Kecamatan Mengwi - Ni Kadek Ayu Dewi Sukartini; I Made Adi Nugraha Tristaningrat; I Ketut Suparya (Cetta: Jurnal Ilmu Pendidikan, 2026)
The low achievement of science learning outcomes on ecosystem material in elementary schools indicates the need for learning media that are more engaging, contextual, and appropriate to students’ characteristics. This condition was found among fifth-grade students in Cluster 2 of Mengwi District, where the achievement of the Criteria for Achieving Learning Objectives (KKTP) was still low, namely 48% at SDN 1 Munggu, 45% at SDN 2 Munggu, 40% at SDN 3 Munggu, 42% at SDN 1 Tumbakbayuh, and 38% at SDN 2 Tumbakbayuh, with an average of 42.6%. This study aimed to analyze the condition of science learning achievement, identify teachers’ and students’ needs for learning media, and describe the urgency of developing a local wisdom-based digital science comic on ecosystem material for fifth-grade elementary school students in Cluster 2 of Mengwi District. This study employed descriptive research with a qualitative approach. Data sources were obtained from fifth-grade teachers, fifth-grade students, learning documents, and KKTP achievement data. Data were collected through observation, interviews, questionnaires, and documentation, and were analyzed through data reduction, data display, and conclusion drawing. The results showed that science learning was still dominated by textbooks and verbal explanations, while teachers and students needed learning media in the form of digital comics containing colorful illustrations, simple storylines, child-friendly characters, systematic ecosystem material, and local contexts such as rice fields, subak, rivers, gardens, and interactions among living things in the surrounding environment. This study concludes that the development of a local wisdom-based digital science comic is highly needed as an alternative learning medium to support students’ understanding of ecosystem material in fifth grade of elementary school.